On the edge — how plant cells monitor growth - Kriechbaum, Choy; Müller, Sabine (Nature Plants, 2024)
Cell edges are part of a coordinate system used by the cell to direct three-dimensional growth in an organized manner. They emerge as signalling hubs with unique composition, capable of sensing mechanical stresses derived from neighbouring cells, to negotiate and harmonize individual cellular growth rates, therefore avoiding mechanical conflict.
CRIS-Team Scopus Importer:2024-03-15